Relating reverse and forward solute diffusion to membrane fouling in osmotically driven membrane processes - She, Qianhong (2013)
Osmotically driven membrane processes, such as forward osmosis (FO) and pressure retarded osmosis (PRO), are attracting increasing interest in research and applications in environment and energy related fields. In this study, we systematically investigated the alginate fouling on an osmotic membrane during FO operation using four types of draw solutions (NaCl, MgCl2, CaCl2 and Ca(NO3)2) to elucidate the relationships between reverse (from draw solution to feed solution) and forward (from feed solution to draw solution) solute diffusion, and membrane fouling. At the same water flux level (achieved by adjusting the draw solution concentration), the greatest reverse solute diffusion rate was observed for NaCl draw solution, followed by Ca(NO3)2 draw solution, and then CaCl2 draw solution and MgCl2 draw solution, the order of which was consistent with that of their solute permeability coefficients. Moreover, the reverse solute diffusion of draw solute (especially divalent cation) can change the feed solution chemistry and thus enhance membrane fouling by alginate, the extent of which is related to the rate of the reverse draw solute diffusion and its ability to interact with the foulant. The extent of fouling for the four types of draw solution followed an order of Ca(NO3)2 > CaCl2 >> MgCl2 > NaCl. On the other hand, the rate of forward diffusion of feed solute (e.g., Na+) was in turn promoted under severe membrane fouling in active layer facing draw solution orientation, which may be attributed to the fouling enhanced concentration polarization (pore clogging enhanced ICP and cake enhanced concentration polarization). The enhanced concentration polarization can lead to additional water flux reduction and is an important mechanism governing the water flux behavior during FO membrane fouling. Findings have significant implications for the draw solution selection and membrane fouling control in osmotically driven membrane processes.